Bone morphogenetic proteins in tissue engineering: the road from laboratory to the clinic: part I (basic concepts) - Bessa, Paulo C. (2008)
Discovered in 1965, bone morphogenetic proteins (BMPs) are a group of cytokines from the transforming growth factor-β (TGFβ) superfamily with significant roles in bone and cartilage formation. BMPs are used as powerful osteoinductive components of diverse tissue-engineering products for the healing of bone. Several BMPs with different physiological roles have been identified in humans. The purpose of this review is to cover the biological function of the main members of BMP family, the latest research on BMPs signalling pathways and advances in the production of recombinant BMPs for tissue engineering purposes.